1987
DOI: 10.1002/jnr.490180206
|View full text |Cite
|
Sign up to set email alerts
|

Receptor‐mediated transcytosis of transferrin across the blood‐brain barrier

Abstract: The perfusion of rat brain with 125I-transferrin resulted in a receptor-mediated uptake of transferrin into the endothelium of the blood-brain barrier followed by its detection in the brain. During a pulse-chase experiment, 125I-transferrin accumulated in the endothelial cells during the pulse, with a decrease of this intraendothelial radioactivity during the chase associated with a concomitant increase in the nonvascular elements of the brain. The receptor-mediated movement of transferrin across the blood-bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
228
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(234 citation statements)
references
References 15 publications
5
228
1
Order By: Relevance
“…This result, together with the presence of a transferrin-mediated vesicle-based transcytosis system through the BBB [19,20,48,49] makes HFt-based NCs potentially good carriers for toxic molecules to the brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This result, together with the presence of a transferrin-mediated vesicle-based transcytosis system through the BBB [19,20,48,49] makes HFt-based NCs potentially good carriers for toxic molecules to the brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Jefferies and colleagues [91] discovered that after injection into the blood, monoclonal antibodies against the TfR labeled the endothelium of brain capillaries but not of other tissues. Further studies showed binding, endocytosis and transcytosis of iodine-labeled Tf by brain capillaries [92,93]. Only 20% of Tf was found to be recycled whereas approximately 50% was transcytosed into the brain parenchyma.…”
Section: Targeting To Various Cell Types Via the Transferrin Receptormentioning
confidence: 98%
“…Since Tf receptors are present on the surface of the cerebral capillaries (Fishman et al, 1985;Jeffries et al, 1984;Partridge et al, 1987) and endocytosis of Tf is known to occur in these capillaries (Partridge et al, 1987), it has been suggested that Mn (in the trivalent oxidation state) enters the endothelial cells complexed with Tf. Mn is then released from the complex in the endothelial cell interior by endosomal acidification and the apo-Tf Tf complex is returned to the luminal surface (Morris et al, 1992a;Morris et al, 1992b) without the assistance of DMT1 (Divalent Metal Transporter-1) (Moos et al, 2006).…”
Section: Manganese Transport Into Brain Transferrin/transferrin Recepmentioning
confidence: 99%